1975
DOI: 10.1002/pssa.2210300129
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature photoluminescence in SnO2 high-resistivity monocrystals

Abstract: Stannic oxide monocrystals behave like photoluminescent emitters over the whole visible range. The emission spectra are measured for temperatures between 29 and 77 K. The shape and the width of emitted band components lead to an analyse of the data by the energy configuration–coordinate model. This quantum scheme is usually developed to describe the behaviour of colour centres in alkali‐halides or phosphors. Two emission bands are selected and analysed in this way, leading to the evaluation of characteristic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

1976
1976
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
2
16
0
1
Order By: Relevance
“…A luminescence band at 2.58 eV could be present as a component in the broadband reported by some authors, e.g., in Ref. 4, but is not normally reported as a resolved band independent of the green and orange bands. In Ref.…”
Section: Discussionmentioning
confidence: 69%
“…A luminescence band at 2.58 eV could be present as a component in the broadband reported by some authors, e.g., in Ref. 4, but is not normally reported as a resolved band independent of the green and orange bands. In Ref.…”
Section: Discussionmentioning
confidence: 69%
“…The electronic energies are determined in this study. [5][6][7][8][9][10][11] Most of these studies showed broad emission bands at ∼600−650 nm (Refs. 3), which is in fairly good agreement with that obtained from the transmittance measurement of bulk SnO 2 (∼3.5 eV at 300 K).…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental absorption edge of SnO 2 · H 2 O is deduced from the diffuse reflectance spectrum to be ∼3.5 eV (Fig. [6][7][8]11 Some studies also showed in bulk SnO 2 very sharp free-and bound-exciton peaks near the band edge at T = 4−15 K (Ref. 3 Let us first discuss about the origin of the R and G emission bands in SnO 2 · H 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have attributed this NIR band to a high surface density of defects states, which is in agreement with the high surface/volume ratio that exhibit the microstructures describe in this work. The orange (1.98 eV) and the green emission (2.25 eV) are associated with oxygen vacancies and complex defects involving oxygen vacancies, while the blue emission (2.58 eV), is related to surface states …”
Section: Resultsmentioning
confidence: 99%
“…The orange (1.98 eV) and the green emission (2.25 eV) are associated with oxygen vacancies [21] and complex defects involving oxygen vacancies, [21] while the blue emission (2.58 eV), is related to surface states. [21,33] The incorporation of Li modifies the CL response by promoting the emission around 1.5 eV, as explained by del Prado et al [29] On the other hand, no sharp lines were observed in the SnO 2 :Li spectrum at about 1.70 eV (729.32 nm) corresponding to 2 S-2 P 0 intraionic transitions due to Li þ in other TCO's such as Ga 2 O 3 or TiO 2 as reported by some authors. [34,35] An allowed transition, 2 P 0 -2 S attributed to Li þ cations, [36] centered at 1.52 eV (815.8 nm) has also been reported.…”
Section: Resultsmentioning
confidence: 99%